THE EFFECTIVENESS OF DESCRIBING PICTURE ACTIVITIES IN IMPROVING STUDENTS SPEAKING ABILITY AT COKROAMINOTO UNIVERSITY PALOPO - Musliadi Musliadi (Institut Agama Islam Negeri Palopo, 2016)
This research describes the effectiveness of expressing present continuous through describing picture in improving the speaking ability of the second semester students of English study program at Cokroaminoto University Palopo. Expressing present continuous through describing picture here is formulated in teaching technique of speaking. It is formulated into series of question using present continuous as the guiding point of speaking for the students to talk about the progress events on the picture. The objective of the research is formulated at finding out whether or not the expressing present continuous through describing picture can improve students speaking ability. The research employs experimental method which applies one group pretest-posttest design. The sample of this research consists of 20 students that are taken through random sampling technique. Based on the result of the data analysis and application of the research, the researcher found that the mean score of posttest (9,3) is greater than the mean score of pretest (5,6). Thats why it can be concluded that expressing present continuous through describing picture which is formulated in teaching technique of speaking improves students speaking ability. They have chance to produce spoken English based on appropriate grammar, especially the present continuous tense.